Impact of Product Differentiation, Culture, and E-Commerce Knowledge on Trust and Intention to Use E-Commerce among MSMEs - Budi, Indah Indah; Solling Hamid, Rahmad; Dewintari, Putri (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose : This study explores the effect of product differentiation, culture, and e-commerce knowledge on trust and intention to use e-commerce among MSMEs in Palopo City. Methodology: It employs a quantitative approach using questionnaires, with data analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Results:  show that product differentiation and e-commerce knowledge have a significant positive effect on trust and intention to use e-commerce, while culture only affects the intention to use e-commerce. Trust mediates the relationship between product differentiation and e-commerce knowledge with intention to use e-commerce. Novelty: of this study lies in its integrative approach, combining multiple factors influencing e-commerce adoption by MSMEs in one model. Finding: It also tests the mediating role of trust, a factor not extensively explored in previous studies on this topic.research contributes to theory by expanding understanding of the variables that affect e-commerce adoption by MSMEs. It also offers practical insights, suggesting MSMEs focus on product innovation and improving e-commerce education to increase competitiveness.Originality: The study’s limitations include its narrow geographic focus and cross-sectional approach. Future research should expand the scope and use longitudinal methods to explore the dynamics of e-commerce adoption. Type of Paper: Empirical Research Paper.